Differences in the metabolite composition and mechanical properties of extracellular vesicles secreted by hepatic cellular models. Issue 1 (1st December 2019) - Royo, Felix; Gil-Carton, David; Gonzalez, Esperanza; Mleczko, Justyna; Palomo, Laura; Perez-Cormenzana, Miriam; Mayo, Rebeca; Alonso, Cristina; Falcon-Perez, Juan M.
ABSTRACT: Liver constitutes the major metabolic factory in the organism and is involved in the synthesis, secretion and clearance of many blood-circulating molecules. Previously, we have characterised the protein and RNA cargo of extracellular vesicles (EVs) secreted by two hepatic cellular models, a mouse hepatocyte progenitor cell line (MLP29) and primary rat hepatocytes (RHs). Here, we report the metabolome profile of these vesicles by performing a targeted UHPLC-MS metabolomics analysis of these two cellular models and their respective secreted EVs. Visual inspection of the data through principal component analysis allows clear separation of the metabolic profile of cells and EVs, and also of both cellular models. Correlation matrix supported that lipid composition of EVs is mainly determined by parent cell composition. EVs derived from MLP29 and RHs showed a negative correlation in their percentage composition of ceramides, glycerophospholipids, sphingomyelins and triglycerides. Metabolites enriched in EVs were also different depending on the cellular model. EVs secreted by MLP29 were enriched in different species of sphingomyelins and ceramides underrepresented in EVs secreted by RHs. Remarkably, triglycerides constitute an important percentage of the composition of EVs derived from RHs. We further investigate if the differences in lipid composition were also accompanied by differences in mechanical behaviour, by using atomic force microscopy complemented with nanoindentation-based methodology. To compare the stiffness and brittleness of EVs derived from MLP29 cell line and RH primary cells, FZ curves were performed in the centre of single vesicles and the differences found in their force- vs.- indentation curves suggest that RHs EVs are softer (less stiff) and less resistance to mechanical failure than MLP29 EVs. Therefore, we can conclude that EVs from different origin carry a characteristic lipid composition related to their parental cell composition, and exhibit different mechanical properties. Abbreviations: For the identification of the different species of lipids, the following abbreviations has been employed: Cer, ceramide; ChoE, Cholesteryl Ester; CMH, monohexosylceramide; DAG, diglycerid; LPC, lysophosphatidylcholin; LPI, lysophosphatidyinositol; PC, phosphocoline; PE, phoethanolamine; PI, phosphoinositol; SM, sphingomyelin; TAG, triglycerid